Telling the Library’s Story: A Personal Reflection - Paul F. Stuehrenberg (Theological Librarianship, 2012)
The author reflects on the circumstances in which he determined that it would prudent to write a history (published in 1992 as A Library Worthy of the School…) of the collections of the Yale Divinity Library, where he has served for many years as Divinity Librarian. These experiences serve as a framework for other librarians to consider whether, or how, they might write histories of the libraries in which they serve. He concludes by identifying what he learned from the exercise.